2020
DOI: 10.3991/ijet.v15i22.17023
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Usefulness of Digital Simulators in the Acquisition of Professional Competencies by Undergraduate Nursing Students

Abstract: Abstract— Digital virtual simulators are considered one of the most innovative teaching methods currently available for overcoming training difficulties in clinical nursing practice. This study aimed to measure the perceived usefulness of digital simulators in the acquisition of professional nursing skills among undergraduate nursing students. A group of 50 students participated in an online training module on a digital simulator over six sessions. They then responded to a survey about the training. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Laschinger et al (2008) found, for example, that "human patient simulators which are used for teaching higher level skills, such as airway management, and physiological concepts are useful". Qaisar et al (2020), in a study of the use of digital virtual simulators as an innovative teaching method, concluded that the vast majority of students found learning with a digital simulator to be an enriching experience and that it would be beneficial to adopt this mode of teaching in other areas of nursing education.…”
Section: )mentioning
confidence: 99%
“…Laschinger et al (2008) found, for example, that "human patient simulators which are used for teaching higher level skills, such as airway management, and physiological concepts are useful". Qaisar et al (2020), in a study of the use of digital virtual simulators as an innovative teaching method, concluded that the vast majority of students found learning with a digital simulator to be an enriching experience and that it would be beneficial to adopt this mode of teaching in other areas of nursing education.…”
Section: )mentioning
confidence: 99%
“…The success of digital-learning depends on many factors like infrastructural accessibility, usage of appropriate methods for teaching learning, adequate course content, student teacher interaction and various methods of assessment. Above all it is important that learners develop a positive attitude for the digital education and its perceived ease of use (Qaisar et al, 2020). Digital classes at times have its own challenges like poor internet access, insufficient digital skills, lack of digital awareness etc.…”
Section: Introductionmentioning
confidence: 99%